Avaliação hemodinâmica e do equilíbrio ácido-básico de fetos transfundidos: análise da substituição progressiva da hemácia do tipo fetal pela hemácia do tipo adulto - Rose Mary de Castro Ranciaro Pereira (2008)
Introduction: The maternal Rh-isoimmunization unchains the perinatal hemolytic illness, that it represents the main cause of fetal anemia. During the treatment with intrauterine transfusion, little is knows from the effect of the concentration of the adult red cells from the blood transfused, in the haemodynamic and the acid-basic equilibrium exchanges of the fetal blood. Objective: To verify the influences of the gradually replacement with higher concentrations of adult red cells during intrauterine transfusion, on fetal haemodynamic and acid- basic equilibrium byevaluation of femoral cardio Index (FCI) and gasometric parameters of fetal venal blood circulation from isoimmunized pregnancies Patients and methods: From April 1998 to January 2007, a longitudinal study was submitted by the Research Ethical Committee (n0 Ex- ETIC 279/04-A-06). The cardiofemoral index (CFI) had been calculated prior to 275 cordocentesis procedures conducted on 85 fetuses. The concentration of fetal hemoglobin determined by the Kleihauer-Betke test and the pH, BE, SO2, HCO3, pO2 and pCO2 levels in venous umbilical blood, weredetermined by the same laboratory. The influence exerted by the concentration of adult red cells on the CFI and the gasometric parameters in fetal blood circulation was evaluated through the univariate and multivariate regression analysis and the significance level considering of 5% for the hypotheses tests. Results: The femoral cardio Index became related of inverse and significant influence to the gradual substitution of the fetal blood by adult red cells. In the univariate analysis(value-p=0,04) and in multivariate regression analysis (value-p= <0,0001) had improvement of cardiac dynamics. The higher concentrations of adult red in fetal circulation influenced direct and significantly the value of pH. Through the univariate linear regression analysis (value p=0,03) and it kept significant as well as in the multivariate regression analysis (value-p=<0,0001), that had coincided with the reduction of acidose. The others gasometrics parameters did not suffered any influence by the gradual substitution of the fetal blood by adult red cells. Conclusions: The gradual transfusion of higher concentrations of adult red cells in the fetal blood circulation had improved the cardiac dynamics evaluated by thefemoral cardio Index and increased the possibility of protection of the cardiac dilatation The improvement of pH was seen by the reduction of the acidemia. These finding evidences the high fetal adaptative capacity to keep the homeostasis, in the correction of the anemia. The fetus that had been more beneficiated of these effects are that had been submitted more the one transfusion.